Optimization of religious extension role in COVID-19 pandemic - Bastomi, Hasan (Journal of Advanced Guidance and Counseling, 2020)
Purpose - Â This study aims to investigate the optimization of the role of religious instructors in the midst of the COVID-19 pandemic.Method - This research is a type of library research, namely, by recording all findings and integrating all findings, both theories and new findings about the religious extension, analyzing all findings from various reading and providing critical ideas about optimizing the role of religious instructors in the midst of the COVID-19 pandemic.Result - The results of the study show that various issues in all sectors emerged as a result of the outbreak of the COVID-19 pandemic, it is necessary to optimize the role of religious instructors who play a very strategic role in the framework of mental, moral, and value development devotion of the people and also contribute to improving the quality of life of the people in various fields both in the field of religion and development amid COVID-19 pandemic by carrying out informative and educative functions, consultative functions, and advocacy functions.Implications - To optimize the role, several things need to be done by religious instructors.Originality - The framework of mental development with optimization of religious extension role in the midst of COVID-19 pandemic.